Kualitas Organoleptik Nasi Instan Berbumbu Dengan Penambahan Puree Buah Naga Merah (Hylocereus polyrhizus) - Aisyah Aisyah; Lilis Sulandari; Nugrahani Astuti; Ita Fatkhur Romadhoni (Journal of Creative Student Research, 2023)
Instant red dragon fruit puree rice is a processed product of seasoned rice added with red dragon fruit puree and then dried. This study aims to determine 1) the effect of adding red dragon fruit puree 2) the interaction effect of the two on organoleptic properties including color, shape, aroma, level of preference for raw instant rice red dragon fruit puree, as well as color, shape, aroma, taste, texture, and preference level of cooked instant rice seasoned with red dragon fruit puree 3) the best product red dragon fruit puree instant rice 4) the chemical content of the best product includes protein, fat, carbohydrates, water and beta-carotene 5) the selling price of the best red dragon fruit puree instant rice. This type of research is an experiment. The independent variable was the addition of red dragon fruit puree (40g, 50g and 60g). Data collection used the observation method through organoleptic tests obtained from 10 trained panelists with instruments in the form of observation sheets in the form of a check list. Data analysis used single analysis of variance (anava) and Duncan's further test with SPSS 17.0. The best product based on organoleptic tests in chemical tests and selling prices using conventional methods. The results showed 1) the addition of red dragon fruit puree had a significant effect on color and the level of preference with (sig: 0.000) instant rice puree raw red dragon fruit and instant rice puree red dragon fruit cooked. 2) Instant red dragon fruit puree rice has no effect on shape, aroma and cooked red dragon fruit puree instant rice has no effect on shape, aroma, taste and texture. 3) the best product is the addition of 50% red dragon fruit puree 4) the content of raw instant rice is higher than the content of cooked instant rice, namely the protein content of raw instant rice is 9.52% and cooked instant rice is 6.90%, the fat content of rice raw instant 4.51% cooked instant rice 3.68%, carbohydrate content of raw instant rice 71.90% and cooked instant rice 52.50%, water content of raw instant rice 12.50% and cooked instant rice 33.10%, and the beta-carotene content of raw instant rice is 56.55%/mg and cooked instant rice is 41.80%/mg. 5) the selling price of instant yellow rice is Rp. 3.726 weight 100 g.